The U-shaped relationship between environmental regulation and carbon emission efficiency: evidence from China’s provincial panel data - Fu, Yisha; Yao, Wentao; Zhang, Xiaoyan; Zeng, Tianyu; Huang, Jiangbao; Han, Guanping; Zeng, Bohan; Li, Yingying (Frontiers in Environmental Science, 2026)
Under the global imperative for energy conservation and emission reduction, a critical yet underexplored question is how environmental regulation (ER) specifically affects carbon emission efficiency (CEE). In this paper, the Super-Slacks-Based Measure (SBM) model with undesirable outputs is used to measure the CEE of 30 Chinese provinces from 2010 to 2022. Based on the results, the Tobit model is used to study the impact of ER on CEE empirically. The results show that (1) China’s CEE is low, and the eastern region has the highest CEE, followed by the central and northeastern regions, and the lowest is the western region. (2) There is a U-shaped curve relationship between ER and CEE, namely, the impacts of ER on CEE are first inhibitory and then promotive; Currently, ER is having a negative effect on CEE, and the inflection point has yet to emerge. (3) Opening up level and population density have positive influences on CEE, while industrial structure exerts a negative impact. This research provides a reference for improving the CEEs of China and other developing countries. Policy implications include the need to strengthen and optimise the regulations to promote the high-quality development of the Chinese economy. The results offer a reference for policymakers.